The longitudinal relationship between hand, hip and knee osteoarthritis and cardiovascular events: a population-based cohort study. Issue 11 (November 2017) - Kendzerska, T.; Jüni, P.; King, L.K.; Croxford, R.; Stanaitis, I.; Hawker, G.A.
Summary: Objective: In this population-based cohort study, we examined the association between the presence of symptomatic osteoarthritis (OA) and risk for cardiovascular (CV) events. Method: A cohort aged ≥55 years recruited from 1996 to 98 was followed through provincial health administrative data to 2014. Demographics, joint complaints and functional limitations were collected. Hip, knee and hand OA were defined using a validated definition. Using Cox-regressions, the relationship between OA and a composite CV outcome (myocardial infarction (MI), stroke, angina, heart failure, revascularization) was assessed controlling for age, body mass index (BMI), sex, pre-existing metabolic factors, comorbidities, income status, primary care exposure and functional limitations. Results: 18, 490 participants were included: median age was 68 years, 60.3% were female; 24.4% met criteria for OA (10.0% hip, 15.3% knee, 16.0% hand), 16.3% self-reported limitation in grip and 25.4% in walking. Over a median 13.4 years, 31.9% experienced a CV event. Controlling for all but walking limitation, a dose–response relationship was observed between number of joints affected by knee/hip OA and CV risk (HR 2 hips/knees vs none: 1.13, 95% CI 1.03–1.23; 3+ hips/knees: 1.22, 95% CI 1.09–1.36). This relationship became non-significant additionally controlling for difficulty walking. Self-reported difficulty walking was associated with a 30% increased hazard for CV events. The effect of hand OA was not significant. Conclusion: In a large population cohort, a greater burden of hip/knee OA was associated with higher CV risk; the relationship was explained by OA-related difficulty walking. Increased attention to management of OA with a view to improving mobility has potential to reduce CV events.